High blood pressure and associated factors in adolescent students - Pinto, José Henrique Duarte; Fonseca, Alenice Aliane; Brito, Maria Fernanda Santos Figueiredo; Pinho, Lucinéia de; Rocha, Josiane Santos Brant; Caldeira, Antônio Prates (O Mundo da Saúde, 2023)
The literature has registered a growing percentage of adolescents with arterial hypertension. This study aimed to analyze the prevalence of high blood pressure (HBP) and identify associated factors among adolescent students. This is a cross-sectional study, with a representative sample of adolescents from public schools in the north of Minas Gerais. Validated instruments covering demographic factors, eating habits and physical activity were used. In addition to blood pressure, data on cardiorespiratory fitness and measurements of visceral fat, overall fat percentage, and body mass index - BMI were collected. After bivariate analysis, the associated variables up to the level of 20% (p ≤ 0.20) were analyzed using logistic regression, assuming a significance level of 5% for the final model. 880 adolescents participated in the study, with a slight predominance of females. The prevalence of HBP was 16.9%. The variables shown to be associated with HBP, after logistic regression analysis, were: high BMI (OR=1.96; 95%CI=1.32-2.89) and male gender (OR=1.45; 95%CI =1.01-2.07). No behavioral or physical fitness-related variables were associated. HBP has a high prevalence among adolescent students and is associated with being overweight and being male.